Teratorn and its relatives – a cross-point of distinct mobile elements, transposons and viruses - Inoue, Yusuke; Takeda, Hiroyuki (Frontiers in Veterinary Science, 2023)
Mobile genetic elements (e.g., transposable elements and plasmids) and viruses display significant diversity with various life cycles, but how this diversity emerges remains obscure. We previously reported a novel and giant (180 kb long) mobile element, Teratorn, originally identified in the genome of medaka, Oryzias latipes. Teratorn is a composite DNA transposon created by a fusion of a piggyBac-like DNA transposon (piggyBac) and a novel herpesvirus of the Alloherpesviridae family. Genomic survey revealed that Teratorn-like herpesviruses are widely distributed among teleost genomes, the majority of which are also fused with piggyBac, suggesting that fusion with piggyBac is a trigger for the life-cycle shift of authentic herpesviruses to an intragenomic parasite. Thus, Teratorn-like herpesvirus provides a clear example of how novel mobile elements emerge, that is to say, the creation of diversity. In this review, we discuss the unique sequence and life-cycle characteristics of Teratorn, followed by the evolutionary process of piggyBac-herpesvirus fusion based on the distribution of Teratorn-like herpesviruses (relatives) among teleosts. Finally, we provide other examples of evolutionary associations between different classes of elements and propose that recombination could be a driving force generating novel mobile elements.